A distinct picornavirus group identified by sequence analysis. - Hyypiä, T (1992)
Although echovirus 22 is presently classified as a member of the enterovirus group in the family of picornaviruses, it has been reported to have exceptional biological properties when compared with other representatives of the group. We have determined the complete nucleotide sequence of the echovirus 22 (Harris strain) genome, which appears to be significantly different from all the other studied picornaviruses. However, the organization of the genome [7339 nucleotides, excluding the poly(A) tract] is similar to that of previously sequenced picornaviruses. This genome includes a 5' untranslated region, relatively well-conserved when compared with aphtho- and cardioviruses, followed by an open reading frame coding for a 2180-amino acid-long polyprotein. The amino termini of capsid polypeptides VP1 and VP3 were determined by direct sequencing, and the other proteolytic cleavage sites in the polyprotein were predicted by comparison with other picornavirus proteins. The amino acid identities of echovirus 22 polypeptides with the corresponding proteins of other picornaviruses are in the 14-35% range, similar to those percentages seen when representatives of the five picornavirus groups (entero-, rhino-, cardio-, aphtho-, and hepatoviruses) are compared. Our results suggest that echovirus 22 belongs to an independent group of picornaviruses.